Implementation of PT Polytama Propindo Community Empowerment Program through the Dapur Usaha Indramayu (Dahayu) - Dwinanto Kurniawan; M. Andri Nugroho; Catharina Siena; Somaya Saragih; Jiwaning Angger Pamukti; Niwang Gita Navulani (Prospect Publishing, 2025)
This paper describes PT Polytama Propindo community empowerment program as part of its commitment to Corporate Social Responsibility (CSR). Dahayu (Dapur Usaha Indramayu) is one of the community empowerment programs for Micro, Small, and Medium Enterprises (MSMEs). Since 2024, it has been implemented in the Juntinyuat District of Indramayu Regency, West Java Province. Dahayu members are a combination of several food-processing MSMEs with products such as soy sauce, salted egg crackers, ranginang, and fried onion. The Dahayu Program is implemented in several phases: planning, implementation, monitoring, and evaluation. The program aims to respond to existing problems and potentials. After studying the Juntinyuat area, we saw that there are a lot of MSMEs, the popularity of Junti soy sauce, and plenty of shallots. However, there are also some problems, such as marketing areas that are limited because the packaging isn't suitable for food and conventional marketing strategies. This program helps upgrade MSMEs by increasing their income and marketing reach for exports through the following: transitioning to food-grade packaging, providing production and marketing tools, regularly training their workers to increase production capacity, assisting them in obtaining business distribution permits, and helping them participate in events.